2014
DOI: 10.4238/2014.may.23.10
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Fas/Fasl, Bcl-2/Bax, and Caspase-8 in rat nonalcoholic fatty liver disease pathogenesis

Abstract: ABSTRACT. The aim of this study was to investigate the roles of Fas/ FasL, Bcl-2/Bax, and Caspase-8 mRNA expressions in nonalcoholic fatty liver disease (NAFLD). The apoptosis percentage was measured by flow cytometry, the immunohistochemical assay was performed for the determination of Fas, FasL, Bcl-2, and Bax expressions, and a real-time polymerase chain reaction (PCR) assay was performed to detect Caspase-8 mRNA expression. Flow cytometry showed that the apoptosis percentage of the rat liver in the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
3
21
0
1
Order By: Relevance
“…Here, we provide first morphological evidence of the overexpression of the proapoptotic protein Bax in hepatocytes of rats following congestive heart failure. These findings are in agreement with the previous demonstration of Bax overexpression-accompanied apoptosis in response to liver injury induced by acetaminophen [ 40 ], liver cancer [ 41 ], psychoactive drug- induced hepatotoxicity [ 42 ], non-alcoholic rat liver disease [ 43 ] or chronic hepatitis [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Here, we provide first morphological evidence of the overexpression of the proapoptotic protein Bax in hepatocytes of rats following congestive heart failure. These findings are in agreement with the previous demonstration of Bax overexpression-accompanied apoptosis in response to liver injury induced by acetaminophen [ 40 ], liver cancer [ 41 ], psychoactive drug- induced hepatotoxicity [ 42 ], non-alcoholic rat liver disease [ 43 ] or chronic hepatitis [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Dysfunction of one organ often leads to a deterioration of function of the other one such as the kidney [ 27 ]. Recently, the investigation of organ crosstalk in acute renal injury reported that cell death, inflammation, cytokine and chemokine overexpression, caspase-mediated apoptotic mechanisms, and oxidative stress might induce distant organ dysfunction [ 28 , 29 ]. Consistently, the progression of heart failure may contribute to gradual toxic injury to renal cells including apoptosis and consequently persistent kidney damage and functional loss [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bernabò et al [6] study based on amphibian reported large lipid droplets in liver histology and ultrastructure after acute exposure to NPE. There is evidence that liver apoptosis, cell proliferation, and related genes, Fas/FasL, Bax/Bcl-2, and Caspase-8 play an important role in the genesis and development of NASH [26] . However, currently there is a paucity of information about the action and mechanism of 4-NP induced hepatic steatosis in rats.…”
Section: Introductionmentioning
confidence: 99%